A Case Series of Successful Root Amputations and Hemisection: Retaining Compromised Teeth with Perio-Endodontic Lesion - Isa, Mohd Nazrin; Ramlan, Nurul Ain; Ayoub, Afzan Adilah; Zainal Ariffin, Muhammad Hilmi (Journal of Dentistry Indonesia, 2024)
Case report: This case report presents three successful approaches for preserving a tooth through root amputation or hemisection. Patients were referred to the Periodontic Department due to mobility of teeth and swelling of the upper left first molar, upper right first molar and lower right first molar with considerably good oral hygiene. Patients were diagnosed with generalized severe periodontitis associated with perio-endodontic lesions. Therefore, non-surgical root canal treatment (NSRCT) was carried out prior to periodontal treatment, followed by surgical root resection (RR) of the distobuccal (DB) root of the upper left first molar, root resection of the distobuccal (DB) root of the upper right first molar, while hemisection and amputation of the distal (D) root was performed on the lower right first molar. Upon 6-month and 1-year review, the teeth were asymptomatic and remained in function. Conclusion: This paper aims to portray the successful management of the period-endodontic lesion in the context of root resection and crown resection as a conservative method for retaining compromised teeth. The ability of RR to prolong the lifespan of compromised teeth and delay the need for more invasive interventions makes it an essential therapeutic option in contemporary dentistry.